Editorial - Schönhärl, Korinna; Schotters, Frederike; Thiemeyer, Guido (Werkstatt Geschichte)
»Über Geld spricht man nicht.« Diese Benimmregel erweist sich beim Blick in die Ver- gangenheit als Illusion. Keineswegs war Geld grundsätzlich ein Tabuthema zwischen- menschlicher Kommunikation. Ganz im Gegenteil: Mit dem Reden über Geld wird dieses mit Bedeutung aufgeladen. Die Autor*innen dieses Themenheftes untersuch en Gelddis- kurse und die Zuschreibungen von Bedeutung an Geld in der internationalen Geschichte.
Keywords: Financial History; Discourse Analysis; History of Money

Reden über Geld (Werkstatt Geschichte)
»Über Geld spricht man nicht.« Diese Benimmregel erweist sich beim Blick in die Vergangenheit als Illusion. Keineswegs war Geld grundsätzlich ein Tabuthema zwischenmenschlicher Kommunikation. Ganz im Gegenteil: Mit dem Reden über Geld wird dieses mit Bedeutung aufgeladen. Die Autor*innen dieses Themenheftes untersuchen Gelddiskurse und die Zuschreibungen von Bedeutung an Geld in der internationalen Geschichte.
Keywords: Financial History; Discourse Analysis; History of Money

Narrating the sound of self: The role of pronunciation in learners’ self-constructions in study-abroad contexts - Müller, Mareike; Schmenk, Barbara (International Journal of Applied Linguistics)
This paper discusses the findings of an empirical study that explores the relationship between study-abroad experiences, learner identity, and pronunciation. We argue that the role of pronunciation as a personal domain of meaning-making warrants more attention than it has hitherto received. To this end, we investigate the narratives of Canadian learners, studying abroad in Germany, in relation to discourses of language learning, culture, and identity, using a Critical Discourse Analysis approach. Our data, which we gained from semi-structured interviews and e-journals, shows that learners’ perceptions of pronunciation are closely linked to their views of the native-speaker ideal, impacting their self-constructions and interpretations of learning experience. In conclusion, we argue for a more differentiated understanding of pronunciation and its implications for language teaching and study abroad.
Keywords: learner identity; study abroad; pronunciation; native-speaker ideal; critical discourse analysis